2017 IEEE International Conference on Software Architecture (ICSA) 2017
DOI: 10.1109/icsa.2017.24
|View full text |Cite
|
Sign up to set email alerts
|

Research on Architecting Microservices: Trends, Focus, and Potential for Industrial Adoption

Abstract: Abstract-Microservices are a new trend rising fast from the enterprise world. Even though the design principles around microservices have been identified, it is difficult to have a clear view of existing research solutions for architecting microservices.In this paper we apply the systematic mapping study methodology to identify, classify, and evaluate the current state of the art on architecting microservices from the following three perspectives: publication trends, focus of research, and potential for indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(138 citation statements)
references
References 15 publications
(30 reference statements)
2
124
0
12
Order By: Relevance
“…We expected this result since model interpretation allows designers to achieve a high level of flexibility, which is more naturally achieved when abstract, platform-independent aspects are considered (rather than, e.g., hardware-specific ones). Nevertheless, given the continuously growing trend of cloud-and container-based solutions [15,16], we may expect that, in the future, interpretation of UML models will consider also platform-and hardwarerelated aspects of the system (e.g., for allowing the system to adapt its structure and behavior at runtime depending on the currently available infrastructural resources).…”
Section: Covered Mda Layers Versus Execution Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…We expected this result since model interpretation allows designers to achieve a high level of flexibility, which is more naturally achieved when abstract, platform-independent aspects are considered (rather than, e.g., hardware-specific ones). Nevertheless, given the continuously growing trend of cloud-and container-based solutions [15,16], we may expect that, in the future, interpretation of UML models will consider also platform-and hardwarerelated aspects of the system (e.g., for allowing the system to adapt its structure and behavior at runtime depending on the currently available infrastructural resources).…”
Section: Covered Mda Layers Versus Execution Strategymentioning
confidence: 99%
“…Note that most tools (16/19) heavily exploit Java, while most academic solutions (41/63) leverage technologies specifically developed for model manipulation (i.e., model transformation languages). Among them, QVT, 15 Acceleo, 16 and ATL. 17 Model-level interactive debugging This parameter specifies whether the analyzed solution provides some level of support for interactive debugging at the level of the source UML model (e.g., support for specifying breakpoints in the models, step-by-step execution at the UML level.).…”
Section: Execution Tools and Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the practical applicability is limited due to its dependence on a "detailed and exhaustive specification of the system" [4]. Microservices architecture as a field "rooted in practice" [16] is widely discussed in industry. It can be expected that further research will very likely reveal new approaches that can be incorporated and thus extend the findings of this study.…”
Section: Resultsmentioning
confidence: 99%
“…Several publications discussing Microservices also cover the aspect of migrating monoliths to Microservice-based architectures to some extent [22,25,29,36], but the topic is still evolving. A systematic mapping study conducted in 2016 identified 3 out of 21 studies dealing with migration topics [31], while Di Francesco et al found 16 out of 71 migrationrelated studies during their review in 2017 [16]. The papers found were mainly solution proposals, followed by experience reports and opinion papers.…”
Section: Related Workmentioning
confidence: 99%